Ollie and Augustus - Evans, Gabriel, 1991- (Newtown, NSW : Walker Books Australia, 2021)
A funny, heartwarming story about little Ollie's determination to make sure his great big dog Augustus is okay when he's at school. Ollie was small - like a pickling jar or a shoe box. Augustus was big - like a fridge or a table. They did most things together, including cycling, painting, dressing up, digging (Ollie's favourite thing) and stick collecting (Augustus's favourite thing). But Ollie is about to start school, and he has one major concern: who will keep Augustus company? He decides to search for a playmate for his enormous companion, but good friends are hard to find, especially for your best mate. In the end, Augustus shows Ollie that he doesn't mind waiting for him and that he can enjoy his time at school, worry-free.
For pre-school age.
Keywords: Dogs -- Juvenile fiction; Dog owners -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; First day of school -- Juvenile fiction; Children's stories; Australian